Transnational spaces: A resource for freedom. The case of pioneer university women - Flecha García, Consuelo (Historia y Memoria de la Educación, 2025)
This article is part of a line of research into transnational women's movements in the decades between the nineteenth and twentieth centuries. On this occasion, it focuses on those young women who, because they were women, were closed to university lectures in their own countries, and were forced to move to where they were accepted. The pioneer in Europe was the University of Zúrich, followed in subsequent years by others in Switzerland, France and Belgium. As sources, in addition to the historiography on this subject, university documentary collections, statistical series, press and testimonies of some of the protagonists have been used, which have provided valuable information to achieve the planned objective of systematising and extending what is known about a reality that was perhaps not expected. More than a thousand female students travelled, from around thirty different geographical origins, to enrol in the degree courses they wished to study. Most of them came from what was then the Russian Empire to study medicine. These pages, attempt to provide an insight into the circumstances that intervened in their itineraries, political and academic, social and family circumstances; and also into the life trajectories shaped by the trips abroad, the intercultural experiences, the awareness they gained of their rights and their subsequent professional practice.